2017
DOI: 10.1007/s10068-017-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscle lysyl oxidase activity and structural/thermal properties of highly cross-linked collagen in jumbo squid (Dosidicus gigas) mantle, fins and arms

Abstract: Muscle from mantle, fins and arms of squid () were compared based on lysyl oxidase activity (LOX), chemical/structural and thermodynamic properties of highly cross-linked collagen. The arms collagen presented the highest temperature (Tp) and enthalpy of transition. The arms collagen thermic properties may be explained by the higher imino amino acid content, proline and lysine hydroxylation degrees. Moreover, among the regions, the collagen from the arms had a more intense β band chain, hydroxymerodesmosine pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Furthermore, the collagen content in the marine organism has been established within a wide range, varying from 3 to 18% in different squid species. [10,[18][19][20][21] Since there is a close relationship between the extraction yield (EY) and CS from jumbo squid muscle, this variability also could be observed in the crosslinking degree of the collagen fibers. [5] In jumbo squid muscle, Sarabia-Sainz et al [19] found a lower solubility in collagen extracted from arms compared to the collagen extracted from fins and mantle.…”
Section: Changes In Collagen Solubility (Cs)mentioning
confidence: 99%
“…Furthermore, the collagen content in the marine organism has been established within a wide range, varying from 3 to 18% in different squid species. [10,[18][19][20][21] Since there is a close relationship between the extraction yield (EY) and CS from jumbo squid muscle, this variability also could be observed in the crosslinking degree of the collagen fibers. [5] In jumbo squid muscle, Sarabia-Sainz et al [19] found a lower solubility in collagen extracted from arms compared to the collagen extracted from fins and mantle.…”
Section: Changes In Collagen Solubility (Cs)mentioning
confidence: 99%
“…, 2018; Sarabia‐Sainz et al . , 2018). The differences on the maximum denaturation temperature (Tmax, °C) could be attributed to various factors such as the protein replacement during the growth of the cephalopod.…”
Section: Resultsmentioning
confidence: 99%
“…, 2015a; Sarabia‐Sainz et al . , 2018). Likewise, the presence of the endothermic transition above the 100 °C confirms the presence of collagen (Torres‐Arreola et al .…”
Section: Resultsmentioning
confidence: 99%
“…During the biogenesis of the connective tissue (CT) matrix, Lox oxidizes the Lys residues in collagen and elastin, thereby initiating the formation of covalent cross‐links that stabilize these fibrous proteins (Smith‐Mungo & Kagan, ). When the Lox activity is high, it will induce a high production of Pyr (Li et al, ; Sarabia‐Sainz et al, ). The Pyr molecule is a very active component of the extracellular matrix that gives stability and hardness to collagen fibers (Eyre & Wu, ).…”
Section: Introductionmentioning
confidence: 99%
“…When the Lox activity is high, it will induce a high production of Pyr (Li et al, 2005;Sarabia-Sainz et al, 2018). The Pyr molecule is a very active component of the extracellular matrix that gives stability and hardness to collagen fibers (Eyre & Wu, 2005).…”
Section: Introductionmentioning
confidence: 99%